Heart Rate Variability as Indicator of Clinical State in Depression - Hartmann, Ralf; Schmidt, Frank M.; Sander, Christian; Hegerl, Ulrich (Frontiers in Psychiatry, 2019)
Background Depression is a severe disease with great burdens for the affected individuals and public health care systems. Autonomic nervous system (ANS) dysfunction indexed by measures of heart rate variability (HRV) has repeatedly been associated with depression. However, HRV parameters are subject to a wide range of multi-factorial influences and underlying mechanisms in depression are still unclear. HRV parameters have been proposed to be promising candidates for diagnostic or predictive bio-markers for depression but necessary longitudinal design studies investigating the relationship between HRV and depression are scarce. Methods The sample consists of 131 matched depressive and non-depressive individuals without antidepressant medication prior to anti-depressive treatment. In a repeated measurements design 15 minutes of resting ECG signals were recorded 1 to 2 days before and 2 weeks after onset of antidepressant treatment. ECG signals were pre-processed to extract inter-beat-intervals. Linear and non-linear methods were carried out to analyze and calculate HRV parameters. Results Analyzes revealed HRV parameter differences between groups of depressive and non-depressive individuals at baseline. Further results show differences in HRV parameters within subject after two weeks of antidepressant treatment. Change in HRV parameter values correlate with changes in symptom severity of depression. Discussion Results provide further insight into the relationship between HRV parameters and depression in a repeated measurements design. HRV parameters are evaluated for potential utilization as indicators for clinical state of depression.